(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
this paper looks into the principles of American pronunciation standards and applications, specifically those of General American, as a model used in teaching the language. The work shall further review how GA has been affecting the reduction of accent and international teaching of the English language, drawing upon phonological features, its development towards a standard language, and reception by native and non-native speakers.